PENGAJARAN MUATAN LOKAL DI SUMATRA BARAT DAN DILEMANYA - Gayatri, Satya (Jurnal Ilmu Budaya, 2009)
Teaching local subjectin some places in Indonesia, particularly, in West Sumatra, faces sorre constraints which causes dillemma in applying it.